A systematic review and qualitative synthesis of the experience of living with colorectal cancer as a chronic illness. Issue 3 (4th March 2022) - McGeechan, Grant J.; Byrnes, Kate; Campbell, Miglena; Carthy, Nikki; Eberhardt, Judith; Paton, Wendy; Swainston, Katherine; Giles, Emma L.
Abstract: Objective: Advances in detection and treatment mean that over 50% of people diagnosed with colorectal cancer can expect to live for more than ten years following treatment. Studies show that colorectal cancer patients can experience numerous physical and psychological late effects. The aim of this study was to conduct a systematic review and qualitative synthesis on the experiences of living with colorectal cancer as a chronic illness. Methods: Electronic searches of online databases were undertaken of peer reviewed and grey literature. Forty-seven papers were eligible for inclusion in the review, capturing the experiences of over 700 participants, the findings from which were analysed using thematic synthesis. Results: Three higher order concepts were identified which were prevalent across studies and countries and which related to the supportive care needs of patients; common physical and psychological late effects of cancer; and methods of psychosocial adjustment to living with and beyond colorectal cancer. Conclusion: The results are considered in the context of existing theoretical approaches to chronic illness and the need to develop a theoretical approach which fully encapsulates the experience of living with colorectal cancer as a chronic illness in order to inform interventions to support patient adjustment.